Implementation of the Project for Strengthening the Profile of Pancasila Students (P5) in Increasing the Independent Attitude Ability of Grade IV Students at SDN 1 Kemawi - Suryati, Suryati; Aryani, Ine Kusuma (Proceedings Series on Social Sciences & Humanities, 2025)
The problem raised in this study lies in the fact that many students still lack independent attitude skills. This problem was clearly seen during the implementation of the Pancasila student profile strengthening project at SDN 1 Kemawi . Based on the results of pre-research interviews, SDN 1 Kemawi implemented three Pancasila student profile strengthening project themes, each of which targeted the independence dimension as one of the main focuses. Independence is one of the most important characteristics that an individual can have. For students, independence plays an important role in their academic journey, because those who learn independently are able to achieve their educational goals without relying on help from peers. At SDN 1 Kemawi , one of the main efforts to foster independent character is through the implementation of the Pancasila student profile strengthening project. This study was conducted to support the project's goal of improving students' independent attitudes. This study uses a descriptive method through a qualitative approach, which was conducted at SDN 1 Kemawi Somagede . The subjects of the study included the Principal, Grade IV teachers , and Grade IV students .Data were collected through observation, interviews, and documentation. Analysis involved data reduction, presentation, and drawing conclusions. The findings showed that the project was successful in improving the independence of Grade IV students. Challenges that emerged during the implementation were handled effectively by the teachers.